Malaysia and Lebanon, 1963-2009: Small state bilateral relations / Ilango Karuppannan - Ilango , Karuppannan (2018)
Studies of the foreign policy behaviour of states have largely neglected the aspect of diplomatic relations between small states. This research attempts to address this gap by examining Malaysia’s bilateral relations with Lebanon, two small, if dissimilar states. This study examines the previously inaccessible diplomatic cables, reports, memoranda, third person notes and other official records of the ministry of foreign affairs of Malaysia, as well as secondary sources and first-hand views of relevant individuals, to construct a compelling account of the development of this relationship from 1963 to 2009. This study revealed critical junctures that cannot be easily explained. A more complete explanation was only possible by taking onto account the influence of a third state on the systemic environment which this thesis has coined as the Third State Effect. The third states investigated in this bilateral relationship are Indonesia and Israel. Diplomatic relations with Lebanon was essential for Malaysia to gain a diplomatic presence in the Middle East to neutralise the campaign of isolation against her mounted by Indonesia and her allies as part of the Konfrontasi. Subsequently, Israel served as the main driver of bilateral relations which in turn served to satisfy other domestic needs. The research makes a significant contribution towards building a corpus of knowledge of Malaysia’s relations with the Middle East. As Lebanon is considered by the Arab states as the geo-strategic front of the Middle East conflict, this study could also shed light into Malaysia’s relations with the other Arab states.